Norwegian Banks' Adjustment to Stricter Capital and Liquidity Regulation - Per Atle Aronsen; Monique E. Erlandsen Erard; Kjell Bjørn Nordal; Lars-Tore Turtveit (Norges Bank, 2014)
Capital and liquidity requirements for Norwegian banks are being gradually tightened. This paper presents the alternatives Norwegian banks have for complying with stricter capital regulation and the forthcoming LCR. Norwegian banks have so far primarily used retained earnings to strengthen their capital and this is also the likely future adjustment choice. The relationship between the level of bank equity and the cost of equity is important for banks' adjustment decisions. It may be reasonable to expect that large Norwegian banks in a steady state will have a cost of equity of about 10 percent and ROE of about 12 percent. We also look into Norwegian banks' current holdings of liquid assets, and strategies that may be used to comply with the LCR. Studies show that the impact on lending margins from complying with the LCR is low and negligible for Norway.
hdl:11250/2506898
Keywords: 330